Academic Scientists at Work - Boss, Jeremy M. author. aut Link
VII, 248 p. 135 illus.
Keywords: Academic Scientists at Work guides the scientist on the journey from the end of a postdoctoral career to the point of promotion to Associate Professor. The book includes valuable advice on: -Choosing and getting your ideal academic job; -Setting up and effectively managing the lab; -Obtaining funds; -Teaching and mentoring; -The promotion and tenure process. Also offered are template worksheets and point-by-point instructions on how to complete them, with downloadable blank worksheet versions contained in the accompanying CD-ROM. Included are six database program files that can be used to help the reader organize his/her laboratory specific reagents. Academic Scientists at Work is a valuable resource for the Career Scientist who demands and expects the best.